Evaluation of different short term aging procedures with neat, warm and modified binders. (1st March 2016) - Dondi, G.; Mazzotta, F.; Simone, A.; Vignali, V.; Sangiorgi, C.; Lantieri, C.
Highlights: Binders modified with polymer and wax were studied. The mixing temperature was evaluated through the equiviscous method. Short Term Aging procedure was studied with RTFOT at 163 °C and mixing temperature. Rheological and chemical properties of unaged and aged bitumens were studied. Abstract: This work is based on the characterization of road materials that combine high performance and reduction of the environmental impact during road construction and maintenance. In particular polymer modified bitumens with and without wax additives have been studied. The first increase the elasto-plasticity of the mixture, increasing its durability and fatigue resistance. As for the second the presence of paraffinic additive reduces the bitumen viscosity and consequently the asphalt mixing and compaction temperatures. A number of studies have shown that the mechanical characteristics of pavement are strongly influenced by the oxidation degree of the organic components of the bitumen during mixing and compaction phases. This phenomenon is known as short-term aging. Binders modified with polymer and wax were analyzed according to the viscoelasticity theory and different aging conditions were simulated. Tests of advanced rheological characterization were carried out by using the Dynamic Shear Rheometer and the short-term aging was simulated by Rolling Thin Film Oven Test. A new procedure of bitumen aging at the equiviscous temperature or T mixing was proposed. Further rheological tests on aged binders were carried out at this temperature. The results have been supported by FTIR (Fourier Transform Infrared Spectroscopy) analytical chemical tests, analyzing the molecular changes on the aged binders. The standard temperature of 163 °C does not correctly simulate the short term aging of polymer modified and waxes bitumens.